Rapid synthesis for monodispersed gold nanoparticles in kaempferol and anti-leishmanial efficacy against wild and drug resistant strains. Issue 23 (2nd March 2017) - Halder, Asim; Das, Suvadra; Bera, Tanmoy; Mukherjee, Arup
Abstract : Synthesis of monodispersed gold nanoparticles using kaempferol and antileishmanial activity with high macrophage uptake capacity. Abstract : Leishmaniasis is a WHO notified neglected tropical disease (NTD) caused by the Leishmania parasite species. The parasite locates rapidly in the macrophage cells and survives there for a long period of time with or without any symptomatic response. Eliminating Leishmania from the macrophage sites is complicated. Only a few antileishmanial drugs are known and most of them have developed resistance over the time. We have synthesized highly monodispersed gold nanoparticles (KAunp) in a rapid reduction reaction catalyzed in kaempferol. Kaempferol stabilized nanoparticles in 18.24 nm size domain were used as leishmanicidals in macrophage infested conditions. KAunps' CC50 in the macrophages was at 2.4 × 10 2 μM while that for sodium stibogluconate was 27 μM. Phagocytic uptake in infested cells was fast and remarkable. KAunps were explicitly effective against both the wild and drug resistant organisms. Monodispersed gold nanoparticles synthesized in green technology appeared as safer alternatives for leishmanial chemotherapy.